BLENDED LEARNING TAXONOMY (International Conference on Social and Islamic Studies, 2021)
The use of information technology in education has undeniable potential to improve teaching quality and learning dexterity. The Covid-19 pandemic that swept the globe, particularly in Indonesia, created havoc, particularly in the school system. The education dilemma brought on by the Covid-19 pandemic has resulted in issues that are inextricably linked to the rise of the digitalization revolution in education. As a result, it is vital to learn utilizing electronic equipment and services known as e-learning. Blended learning is one of the e-learning models that can be employed in online learning. Blended learning is defined as a formal education program that includes times when students study content online and times when teaching is overseen in the classroom. This study offers a survey of the literature and research on the taxonomy of blended learning as follows: (1) The obstacles associated with blended learning are culture and blended learning environment, finding the correct design, time constraints, well-integrated teamwork, and communication. (2) blended learning based on web-support such as linking-the-lecturer curates, wrapping-the-lecturer guides, wisc-online, khan academy, VLE/LMS, PLE, personal learning networks, mashups, and mupples; (3) blended learning based on websupport such as wisc-online, khan academy, VLE/LMS, PLE, personal learning networks, mashups, and mupples.